The Impact of Government Regulation on Risks in Banking - Yuliia KOVALENKO; Halyna KRYSHTAL; Iryna CHUNYTSKA; Alexander VOLOSHANYUK (Communications of International Proceedings, 2021)
The article reveals topical issues of state regulation of banking risk in Ukraine. Purpose. The purpose of the article is to assess the impact of state risk regulation in the banking sector on Ukrainian social and economic spheres and provide suggestions for taking into account not individual methods and aspects of financial risk assessment, but the problem of measuring risks in the complex. There should be a comparison of the amount of capital calculated on the basis of the standard approach of Basel II and the structural model, as well as a comparison of the size of short-term liquidity and increased stable long-term financing in accordance with the requirements of Basel II. Methods. The article is based on general scientific methods of cognition especially on such as analysis and synthesis, induction and deduction, system-structural method, quantitative and qualitative comparison, grouping, method of logical generalization. Results. The article considers dynamics of financial risk factors of the banking sector and the volume of portfolios that are exposed to risk, in terms of yield on loans in the social and economic spheres, the value of its deposits, the profitability of the market portfolio of securities of banks, the share of administrative costs in the banking sector. There were built the models for each financial risk factor. There were parametric approximations of their historical. Conclusion. The stress test confirmed the urgency of the task of increasing the capital adequacy of the banking sector, which in the face of negative systemic changes must resist the decline in quality and increase the volatility of return on assets.
Keywords: Government Regulation; Banking Sector; Socio-Economic Sphere; Risks; Capital